Self-assembling ferritin nanoplatform for the development of infectious hematopoietic necrosis virus vaccine - Ahmadivand, Sohrab; Krpetic, Zeljka; Martínez, Merce Márquez; Garcia-Ordoñez, Marlid; Roher, Nerea; Palić, Dušan (Frontiers in Immunology, 2024)
Self-assembling protein nanoparticles are used as a novel vaccine design platform to improve the stability and immunogenicity of safe subunit vaccines, while providing broader protection against viral infections. In this study, by genetically fusing the virus glycoprotein to the H. pylori ferritin as a scaffold (FerritVac), we constructed a self-assembling Infectious Hematopoietic Necrosis Virus (IHNV) nanovaccine. IHNV is a WOAH-listed disease for which there are currently no therapeutic treatments and no globally available commercial vaccine. Despite the introduction of an exogenous fragment, the FerritVac NPs show excellent stability same as Ferritin NPs under different storage, pH and temperature conditions, mimicking the harsh gastrointestinal condition of rainbow trout, the main IHNV host. MTT viability assays showed no cytotoxicity of FerritVac or Ferritin NPs in zebrafish cell culture incubated with different doses of up to 100 µg/mL for 14 hours. In trout head kidney macrophages, FerritVac NPs upregulated expression of innate antiviral immunity, IHNV and other fish rhabdovirus infection gene markers (mx, vig1, ifit5 and isg-15). This novel vaccine nano-self-assembly approach offers significant commercial potential for non-mammalian viruses and the control of fish viral diseases. In this study, we demonstrate the development of a soluble recombinant glycoprotein of IHNV in the E. coli system using the ferritin self-assembling nanoplatform, as a biocompatible, stable and effective foundation to rescue and produce soluble protein and enable oral administration and antiviral induction for development of a complete IHNV vaccine.